2004
DOI: 10.1093/ndt/gfh420
|View full text |Cite
|
Sign up to set email alerts
|

Midodrine appears to be safe and effective for dialysis-induced hypotension: a systematic review

Abstract: This systematic review would suggest that midodrine has a role in the therapy of haemodialysis patients experiencing IDH. This conclusion must be viewed with caution, however, given the quality and sample size of the studies included in this review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(106 citation statements)
references
References 15 publications
1
104
1
Order By: Relevance
“…It has been safely and successfully used in patients with end-stage kidney disease whose hypotension would otherwise have compromised chronic dialysis. 15 Furthermore, it was successfully used to treat hypotension secondary to stunned myocardium post-infarction. 16 Its use in patients with HF is not known.…”
mentioning
confidence: 99%
“…It has been safely and successfully used in patients with end-stage kidney disease whose hypotension would otherwise have compromised chronic dialysis. 15 Furthermore, it was successfully used to treat hypotension secondary to stunned myocardium post-infarction. 16 Its use in patients with HF is not known.…”
mentioning
confidence: 99%
“…Alt ho ugh it has been shown that mi dod ri ne, an oral se lec ti ve alp ha-1 ad re ner gic ago nist, ef fecti vely pre vents hypo ten si on du ring HD in so me recent stu di es, 2,3,8,[16][17][18] only two stu di es ha ve be en re por ted which des cri be its ef fects on HD pa ti ents with chro nic hypo ten si on. 5,9 This disagreement may be re la ted to cha rac te ris tics of the pa ti ent popu la ti on, study de sign and the do se of mi dod ri ne given.…”
Section: Discussionmentioning
confidence: 99%
“…7 Mo re re cently, mi dod ri ne, an oral se lec ti ve alp ha-1 ad re ner gic ago nist, has be en success fully used in the tre at ment of di aly sis hypoten si on, es pe ci ally in com bi na ti on with co o ling di aly sa te. 8 Ho we ver, the re is li mi ted ex pe ri en ce with the use of mi dod ri ne in HD pa ti ents with chro nic hypo ten si on, even no ex pe ri en ce with dia be tic sub set of HD pa ti ents. 1,5,9 For this re a son, we tri ed to de mons tra te the ef fect of mi dod ri ne tre at ment on di a be tic HD pa ti ents with chro nic hypo ten si on.…”
mentioning
confidence: 99%
“…Furthermore, this drug is beneficial in preventing or ameliorating the symptoms of intradialytic hypotension (Prakash et al, 2004). There are many reports regarding the pharmacological and clinical effects of midodrine, but its pharmacokinetic properties, especially the mechanism behind its intestinal absorption, have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%